Metabolomics Analysis Reveals the Differences Between Bupleurum chinense DC. and Bupleurum scorzonerifolium Willd. - Qu, Xuejie; Hu, Shanqun; Li, Tong; Zhang, Jiaqi; Wang, Baoshun; Liu, Changli (Frontiers in Plant Science, 2022)
Bupleurum chinense DC. and Bupleurum scorzonerifolium Willd. are two varieties of Bupleuri radix in Chinese Pharmacopoeia 2020. Clinical efficacy of the two bupleurum species is different. The difference in clinical efficacy is closely related to the composition of plant metabolites. In order to analyze the difference of metabolites, we used liquid chromatography coupled with mass spectrometry (LC-MS) for untargeted metabolome and gas chromatography coupled with mass spectrometry (GC-MS) for widely targeted metabolome to detect the roots (R), stems (S), leaves (L) and flowers (F) of two varieties, and detected 1818 metabolites in 25 classes. We performed statistical analysis of metabolites. Differential metabolites were screened by Fold Change and VIP values of OPLS-DA model and significant differences were found among different groups. The active components triterpenoid saponins in BcR were more than BsR. Other pharmacological metabolites were significantly different. By KEGG annotation and enrichment analysis, we found that differential metabolites of the aboveground part mainly concentrated in monoterpenoids biosynthesis, while the differential metabolites of the root mainly concentrated in sesquiterpenoid and triterpenoid biosynthesis. Differences in metabolic networks may indirectly affect the metabolic profile of Bc and Bs, leading to differences in clinical efficacy. Our study provides scientific basis for subsequent biosynthesis pathway and related bioactivity research, and provides reference for developing non-medicinal parts and guiding clinical application of Bupleuri Radix.